Peran Tradisi Keagamaan dalam Membangun Karakter Moderat di Sekolah Islam - Ahmad Purwanto (TA'DIB: Jurnal Pendidikan Agama Islam, 2025)
Religious traditions in Islamic schools have an important role in shaping the moderate character of students. Religious moderation is an essential value in dealing with diversity and preventing extreme attitudes in religious life. This study aims to analyze how religious traditions in Islamic schools contribute to building students' moderate character, with a focus on the values of inclusivity, tolerance, and balance in religious understanding. This study uses a qualitative approach with the library research method. Data were collected through observation, in-depth interviews, and analysis of related documents. The results of the study show that various religious traditions, such as the commemoration of Islamic holidays, routine recitations, and congregational worship practices, contribute to instilling the values of religious moderation. In addition, the involvement of teachers and the school environment in internalizing the values of togetherness and respect for differences is a key factor in building the moderate character of students. Thus, this study confirms that religious traditions in Islamic schools not only function as religious practices, but also as an effective means of shaping the character of moderate, inclusive, and tolerant students. The results of this research are expected to be a reference for the development of Islamic education policies based on the values of religious moderation.